Social customer relationship management: An integrated conceptual framework - Dewnarain, S.; Ramkissoon, Haywantee; Mavondo, F. (Routledge, 2018)
© 2018, © 2018 Taylor & Francis Group, LLC. In recent years, the concept of customer relationship management (CRM) has undergone a major change from being a strategy that focused solely on establishing financial bonds with customers to one that promotes both transactional and interactional relationships with customers. This has given rise to a new form of CRM which is known as social customer relationship management (SCRM) or CRM 2.0. Hence, this study develops and proposes a conceptual model to address relationships between customer relationship management, social media technologies, customer engagement, positive word of mouth and brand loyalty. This paper brings significant contributions to hospitality CRM literature and marketing communication theory. It serves as a reference for hospitality practitioners who can derive insights on the potential economic advantage such as brand loyalty and consumer behaviour benefits in the form of positive word of mouth which can result from the effective implementation of a SCRM strategy.